1993
DOI: 10.1039/c39930000661
|View full text |Cite
|
Sign up to set email alerts
|

Molecular tapes based on CN ⋯ Cl interactions

Abstract: Weak C=N.-CI interactions may be used to design linear molecular tapes.The construction of molecular ensembles, utilising the directional characteristics of intermolecular forces, is one of the key elements of contemporary supramolecular chemistry. 1 Linear or zig-zag arrays of flat molecules have been described by Lehn2 and by Whitesides3 who has referred to such arrays as 'molecular tapes'. Tapes, such as those found in the crystal structures of molecular complexes of substituted aminopyrimidines or melamine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
39
0
2

Year Published

1997
1997
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 8 publications
0
39
0
2
Order By: Relevance
“…[22] The N···Cl distances are typically 3.00Ϫ3.45 Å . [23] When the nitrogen atom is present in an aromatic ring the N···ClϪC angle tends to be around 180°depending on distortions induced by crystal packing. A computational study has estimated the energy of association for N···Cl at around 5 kJ mol Ϫ1 .…”
Section: Crystal Structure Of 12·(chcl 3 )mentioning
confidence: 99%
“…[22] The N···Cl distances are typically 3.00Ϫ3.45 Å . [23] When the nitrogen atom is present in an aromatic ring the N···ClϪC angle tends to be around 180°depending on distortions induced by crystal packing. A computational study has estimated the energy of association for N···Cl at around 5 kJ mol Ϫ1 .…”
Section: Crystal Structure Of 12·(chcl 3 )mentioning
confidence: 99%
“…The attractive interactions between halogens and atoms that have lone electron pairs have been known for some time (e.g. Halogen bonds have been utilized successfully in the creation of supramolecular systems; for example, it has been shown that these interactions can create molecular tapes (Reddy, Panneerselvam et al, 1993) or a diamondoid structure (Reddy, Craig et al, 1993). This interaction was termed halogen bonding (Dumas et al, 1983; Legon, 1998), in order to stress some geometrical correspondences with hydrogen bonding, for instance the striking tendency towards the linearity of the CÐXÁ Á ÁY system [for reviews, see, for example, Legon (1999) and Metrangolo et al (2005)].…”
Section: Commentmentioning
confidence: 99%
“…The molecule of (I) is almost planar, the plane of the nitro group making a dihedral angle of 6.97 (7) with the mean plane of the imidazole ring. Halogen bonds have been utilized successfully in the creation of supramolecular systems; for example, it has been shown that these interactions can create molecular tapes (Reddy, Panneerselvam et al, 1993) or a diamondoid structure (Reddy, Craig et al, 1993). the supramolecular architecture of molecular crystals) via interactions with the electron pairs of other atoms, interactions with other halogen atoms or acceptance of weak hydrogen bonds.…”
mentioning
confidence: 99%
“…Recently, I-• .O2N--R contacts (Desiraju, Pedireddi, Sarma & Zacharias, 1993) and cyano...halogen interactions (Reddy, Panneerselvam, Pilati & Desiraju, 1993;Desiraju & Harlow, 1989) have all been identified as influencing spatial orientation of substituted aromatic solids.…”
Section: Looking Fi)r That Molecular 'Glue'mentioning
confidence: 99%